1997
DOI: 10.1007/s11746-997-0031-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of furanoid esters in soybean oil and the effect of variety and environment on furanoid ester content

Abstract: An improved method was developed to analyze the major furanoid esters in soybean oil. The method is based on urea fractionation of the methyl esters, silver ion chromatography, and gas chromatography of the furanoid concentrate. Activation of the soybean lipoxygenase decreased the amount of furanoid ester recovered from the oil, but the degumming of crude soybean oil and the choice of solvent used to extract soybean lipids caused no change in furanoid ester content. Fifty-six soybean varieties, representing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…These amounts were low, but comparable with those of other lipophilic antioxidants like vitamin E [20]. Comparably high FuFA concentrations of 16-65 mg/100 g FAMEs were detected in soybeans [19,21]. Wu et al reported FuFA contents of 16-49 mg/100 g FAMEs (9D5 and 11D5) in soybeans harvested in autumn [19].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…These amounts were low, but comparable with those of other lipophilic antioxidants like vitamin E [20]. Comparably high FuFA concentrations of 16-65 mg/100 g FAMEs were detected in soybeans [19,21]. Wu et al reported FuFA contents of 16-49 mg/100 g FAMEs (9D5 and 11D5) in soybeans harvested in autumn [19].…”
Section: Introductionmentioning
confidence: 82%
“…For instance, soybeans harvested in springtime were richer in FuFAs than soybeans harvested in autumn (e.g. 17 vs. 27 mg/100 g FAMEs for the same variety and growing site) [19]. Guth and Grosch found comparable values of 26-42 mg/100 g FAMEs in soybean oil extracted from soybeans in their laboratory [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations